The Influence of Coping Strategy, Loneliness, and Sleep Quality on Student’s Depression During Covid-19 Pandemic - Yufi Adriani; Audia Ayu Ramadhanti; Worawach Tungjitcharoen (‎‎‎TAZKIYA Journal of Psychology, 2023)
This study aims to examine the effect of the variable coping strategy, loneliness, and sleep quality on symptoms of depression in college students during the Covid-19 pandemic. The authors hypothesized that coping strategy, loneliness, and sleep quality had significant effects on symptoms of depression in students during the Covid-19 pandemic. The population in this study was students who domiciled in Greater Jakarta and were undergoing online lectures during the Covid-19 pandemic. A sample of 203 students were recruited using purposive sampling. The measuring instrument consisted of the Beck Depression Inventory-II scale, The Brief COPE scale, the De Jong Gierveld Loneliness Scale, and The Pittsburgh Sleep Quality Index scale. We tested the validity of the instrument using the Confirmatory Factor Analysis (CFA) technique. The data were analyzed using multiple regression techniques. The results of hypothesis testing indicated that four variables, namely problem-focused coping, emotional loneliness, social loneliness, and sleep quality, significantly influenced symptoms of depression. This study's results showed significant effects of coping strategy, loneliness, and sleep quality on depression symptoms in college students during the Covid-19 pandemic, 52.3%. Meanwhile, avoidant, emotionfocused, and socially-supported coping did not significantly affect students' depression symptoms during the Covid-19 pandemic.